1986
DOI: 10.1007/bf00273402
|View full text |Cite
|
Sign up to set email alerts
|

Urinary β2-microglobulin early indicator of high dose cisdiamminedichloroplatinum nephrotoxicity? Influence of furosemide

Abstract: To evaluate the efficacy of beta 2-microglobulin as an indicator of cisplatinum nephrotoxicity, creatinine clearance and urinary beta 2-microglobulin were measured in 19 patients during 5 h after administration of a single dose of 80 mg/m2 cisplatinum. Eleven patients received furosemide as a concomitant therapy. Serum creatinine and beta 2-microglobulin remained unchanged. A decrease of creatinine clearance was observed. Urinary beta 2-microglobulin increased between 1 and 3 h after administration. This sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Carboplatin is also primarily eliminated by the kidneys [30] and may compete with melphalan for renal clearance. Platinum therapy has also been known to induce renal damage [31]. In one series, half the patients developed reduced GFR during carboplatin therapy [32].…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin is also primarily eliminated by the kidneys [30] and may compete with melphalan for renal clearance. Platinum therapy has also been known to induce renal damage [31]. In one series, half the patients developed reduced GFR during carboplatin therapy [32].…”
Section: Discussionmentioning
confidence: 99%
“…37 In one study, patients that had abnormal increases in urinary B2M did not subsequently develop nephrotoxicity. 38 One reason could be that increased systemic production of B2M may occur in the presence of underlying malignancy. Several studies have shown that baseline urinary B2M concentrations are elevated in cancer patients who have not received chemotherapy, compared to healthy volunteers.…”
Section: Beta-2-microglobulinmentioning
confidence: 99%
“…35 While most of these studies have focused on urinary B2M excretion, it is important to note that serum B2M does not change significantly following cisplatin therapy. 38…”
Section: Beta-2-microglobulinmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients tested showed increased levels of urinary β 2 -microglobulin, a sensitive marker of renal tubular damage. 27 …”
Section: Molecular and Biochemical Findings In Asymptomatic Newbornsmentioning
confidence: 99%